Stylistic Analysis on Selected Literary works of Alicia Tan-Gonzales - Tribunal-Nemenzo, Ruth (International Journal of Humanities and Education Development (IJHED), 2023)
This study looked into the stylistic analysis of the selected literary works of Alicia Tan-Gonzales. Specifically, this study analyzed three of her Hiligaynon literary works using frameworks for stylistic analysis. Using descriptive research design, this study examined phonetic structures and figures of replacement in the poem, Sentensya (Sentence); semantic structures and stylistic deviations in the short story, Mga Luha Para Kay Tatay Jose (Tears for Papa Jose); and turn-taking patterns and topic control that determined power and politeness strategies in the play, Pinustahan Nga Gugma (Betting Love). The stylistic analysis of the poem reveals that (1) for phonetic structures, the rhythmical description and effect of the syllables depended on the divisions of the word structure and grammatical structure; (2) for metrical structures in the poem, unstressed syllables were predominantly used rather than stressed syllables; and (3) for figures of replacement, the significant use of metonymy gave the poem an exaggerated impact. The stylistic analysis of the short story shows that (1) semantic structures based on emotive meaning disclosed the inner mind of the characters; (2) expressive meanings exposed the negative emotional state of the characters; (3) evaluative meanings depicted the characteristics and choices of a strong family woman in society; and (4) as to the reduction on sentence constructions, nominative sentences and ellipsis were evident in the short story, while simple repetition was present, indicating redundancy of sentence construction. The stylistic analysis of the play indicates that (1) the characterizations of different strong women made intuitive descriptions of power based on turn-taking patterns and topic control, although they may not be true in all circumstances in the conversations; and (2) politeness strategies were evident in the play, with positive politeness strategies as the most frequently used, followed by bald on-record, negative politeness, and off-record. Based on the overall results of the study, an instructional module in teaching Stylistics was designed to help students understand the literary style of Alicia Tan-Gonzales in fashioning her selected literary pieces, as well as styles of other literary writers.